MANAGEMENT PROBLEMS OF RURAL DEVELOPMENT IN FRUŠKA GORA - Đukić, Sanja; Glavaš-Trbić, Danica; Banjac, Nikola (Economics of Agriculture, 2017)
This paper analyzes the determinants upon which the successful management of the rural development of Fruška goras area is depended, bearing in mind the presence of national park. The specifc characteristic of Fruška goras area has a multiple influences on the choice of optimal model for rural development. For this purpose, the survey was conducted in 2014. in the area of Fruška gora on a sample of 117 interviewees from this area. Statistical methods are used in order to reach conclusions on the basis of data obtained from survey research. The research results show that in this region dominance of agriculture and tourism is present, with unsatisfactory rural infrastructure. Socioeconomic determinants are key disadvantages affecting the management of rural development of Fruška goras area. The authors conclude that in the future the management model of rural development of Fruška goras area should focus on the development of organic agriculture and rural tourism on a sustainable basis together with rural investments.